Fungos micorrízicos arbusculares no desempenho hortícola de Physalis peruviana L., composição química e bioatividade de extratos dos frutos no controle de mofo-cinzento de morango - Filippi, Débora (2021)
Arbuscular mycorrhizal fungi (AMF) used in the cultivation of goldenberry plants (Physalis peruviana L.), sources of phytochemicals, can improve the antifungal action exerted by fruit extracts and become an alternative in the control of gray mold. This work aimed to verify if AMF, added to the goldenberry cultivation substrate, differ in the horticultural performance of the plants and in the action of the extracts obtained from the fruits in the control of gray mold, and to develop a set of standard area diagram (SAP) to aid the evaluation of gray mold in strawberries. Two experiments were carried out at the Plant Ecophysiology and Phytopathology Laboratories, and at the UPF Horticulture Sector. In experiment I, it was investigated whether plants grown in the absence and presence of AMF differ in terms of root system growth, production, chemical quality and fruit maturation time, identify the presence of phenolic acids and flavonoids in goldenberry fruit extracts and test them. about the in vitro control of gray mold in relation to the use of a chemical fungicide. Three treatments (Rhizophagus clarus, Glomus intraradices and mycorrhizal community) were tested in comparison to plants without mycorrhizal inoculation, in randomized blocks, with five replications. For the phytochemical profile, twenty extracts of goldenberry fruits were used, from the four treatments described above. For the control of gray mold, eight treatments were tested, arranged in a completely randomized design, in replicates, with ten plates per treatment. The isolate G. intraradices showed greater capacity to infect plant roots. R. clarus provided greater root volume to the plants, but did not differ from plants mycorrhizal with G. intraradices. Plants inoculated with the mycorrhizal community showed a greater amount of fine roots, although they did not differ from those produced with the fungal isolates. Non-mycorrhizal plants produced fruits with higher average fresh mass compared to plants inoculated with the mycorrhizal community, but they did not differ from plants mycorrhizal with G. intraradices and R. clarus. The sweetest and most flavorful fruits were produced by plants inoculated with the mycorrhizal community and with the isolate R. clarus. In all extracts the phenolic acids pcoumaric and caffeic and the flavonoid rutin were identified, however, none of the extracts showed better in vitro control of gray mold compared to the chemical fungicide, thus demonstrating that at a concentration of 300 mg/mL, the phytochemicals have no in vitro action on strawberry gray mold. Experiment II aimed to develop and validate a set of SAP to assess the severity of gray mold in strawberries. Ten raters were selected to validate the diagrams, divided into two groups: i) inexperienced raters and ii) with experience in the assessment of plant diseases using rating scales or diagrams. The evaluations and validation took place in three stages: in the first, the evaluators analyzed 50 photos of strawberries with different levels of gray mold severity, presented randomly in Power Point®; in the second stage, they used the scale by Nunes et al. (2012); and in the third, the diagrams developed in this study. The diagram developed allowed a more accurate estimate of the disease. Precision was demonstrated by the proximity between the values obtained by repeatability in the evaluations.